"God, Intelligent Design & Fine - Tuning" - Behe (Michael J); Singh (T D) ("RC/8 Raghunathpur, Manasi Manjil Bldg, VIP Road, Kolkata 700 059-,33 2500 9018info@binstitute.org", 2005)
Religion. Theology
20
Keywords: Religion. Theology